Passive On-Chip Components for Fully Integrated Silicon RF VCOs - Aristides Kyranas; Yannis Papananos (Active and Passive Electronic Components)
In this work integrated passive devices used in RF VCOs are presented. The operation of on-chip inductors and variable capacitors is outlined along with simple electrical equivalent circuits suitable for hand calculations. Design examples of passive devices operating at 5 and 6 GHz in a commercial HBT BiCMOS process are also presented. The parallel resonator quality factor is computed as a function of inductor L capacitor C and their respective losses RSL and RSC .